PERSEPSI ISLAM TENTANG PENDIDIKAN BAGI PEREMPUAN YANG BERKEADILAN GENDER - Andi Warisno (Ri'ayah: Jurnal Sosial dan Keagamaan, 2016)
Social construction in society which proposed as superior is stereotype concept that has meaning woman as domestic workers and men as breadwinner at outside (public workers). The problem of inequality between women and men in employment area cause imbalance gender direct to reconstruction and reformulation of social system and religion which close to Islamic ideal ambition, that is justice. The key mission of Al Qur’an and As Sunnah is freeing humanity from anarchy, inequality, and injustice. In this case, if there is different interpretation based on justice principles and human rights, it should be revisited. Allah is Justice (al-‘Adl), His scripture must right. The struggle of woman position (muslimah) is not enough only from their thoughts, making theory/concepts, but also needed collective effort from the result of study, investigation, social analysis, education and advocacy.